การพัฒนารูปแบบการจัดการเรียนรู้เพื่อพัฒนาความสามารถในการถ่ายโยงองค์ความรู้ทางศิลปะ ของนักศึกษาศิลปศึกษา - จันทน์หอม ประไพลิน; บุญญานันต์ โสมฉาย; ไตรวิจิตรคุณ ดวงกมล (Journal of Education Studies, Chulalongkorn University, 2019)
The aims of this study were 1) to develop a learning management model to improve the ability in transferring art knowledge to art education students, and 2) to report the result from using this model. This model consists of the principles of the model, procedures and an evaluation of before and after using this model in the classroom. Thirty 4th year art education students from the Faculty of Education at Chiang Mai University, has all of whom were studying in the teaching course, were included in this study. They were divided into two groups according to their grading. Their abilities to transfer knowledge were tested. The Switch-replication design was utilized. The model was introduced to the experimental group and then both groups were tested. The results from the ﬁrst group led to a modiﬁcation of the model before being introduced to the second group and both groups. The results can be summarized as follows: 1) the developed model can improve the ability to transfer art knowledge to art education students; 2) the modiﬁcation of the model from the experimental group to be used in the control group did not signiﬁcantly improve their scores; and 3) the ability to transfer knowledge in the experimental group appeared to be sustainable.